2017
DOI: 10.1089/jwh.2016.6128
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Body Mass Index: Using Anthropometric Measures and Body Composition Indicators to Assess Odds of an Endometriosis Diagnosis

Abstract: In a surgical cohort, endometriosis was inversely associated with anthropometric measures and body composition indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 73 publications
2
31
1
1
Order By: Relevance
“…Linear regression using Brobust^standard errors were used to estimate the beta coefficients (β) with a 95% confidence interval (CI) and logistic regression models were used to estimate odds ratios (OR) with a 95% CI. The analysis was adjusted a priori for patient age, body mass index (BMI), race (white vs. non-white), and smoking history due to the known effect between these demographic characteristics and markers of ovarian reserve [16][17][18][19]. Each group was further subdivided into SART age groups for analysis of baseline AMH.…”
Section: Methodsmentioning
confidence: 99%
“…Linear regression using Brobust^standard errors were used to estimate the beta coefficients (β) with a 95% confidence interval (CI) and logistic regression models were used to estimate odds ratios (OR) with a 95% CI. The analysis was adjusted a priori for patient age, body mass index (BMI), race (white vs. non-white), and smoking history due to the known effect between these demographic characteristics and markers of ovarian reserve [16][17][18][19]. Each group was further subdivided into SART age groups for analysis of baseline AMH.…”
Section: Methodsmentioning
confidence: 99%
“…Endometriosis is a dynamic and complex disorder, involving the interplay of genetic and environmental factors. The current review revealed a number of risk factors for endometriosis, including early menarche,[43] increased BMI,[444546] environmental factors (including cigarette smoking),[47] and genetic factors. [4849] It seems some of our findings were consistent with other studies that early menarche, shorter menstrual length, duration of infertility, and family history of endometriosis are strongly associated with endometriosis,[85051] while higher parity and higher BMI are associated with decreased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested that women with a low BMI are at greater risk of endometriosis. [8444546] This might explain the difference in the prevalence in Asian women compared to women from the United States,[11] given that average BMIs are much higher in the US population. However, a critical question is whether the low BMI is the cause or the consequence of developing endometriosis even though these studies suggested a correlation.…”
Section: Discussionmentioning
confidence: 99%
“…ENDO is inversely associated with BMI across the life course and with more favorable morphometric indicators and body composition (Backonja et al 2017, Farland et al 2017. Specifically, lower BMI is suggested to constitute a risk factor for the development of ENDO and a predictive factor for severe ENDO.…”
Section: Predisposition and Body Mass Indexmentioning
confidence: 97%